Virtual Reality as a novel educational tool in pre‐clinical paediatric dentistry training: Students' perceptions. Issue 6 (4th May 2020) - Zafar, Sobia; Lai, Yvonne; Sexton, Christopher; Siddiqi, Allauddin
Abstract: Background: Dental students are required to demonstrate competency by pre‐clinical simulated practice before performing invasive clinical procedures on patients. The Moog Simodont ® Dental Trainer provides a virtual reality‐based dental simulation environment for training students. Aim: This cross‐sectional questionnaire‐based study compared students' perception of the pre‐clinical paediatric dentistry training gained in Simodont ® and conventional simulation environment. Design: The dental students who completed pulpotomies and stainless steel crowns (SSCs) training in Simodont ® and conventional pre‐clinical simulation laboratory were invited to complete a questionnaire on their experience in both environments. The percentages for the distribution of responses to statements about training modality were tabulated, and intra‐participant comparisons were used to measure student preference for either Simodont ® or conventional simulation training. Results: One hundred students completed the survey. Fifty‐one per cent of students agreed that using Simodont ® assisted their learning, and 56% felt Simodont ® training facilitated their understanding of paediatric dentistry tasks. Generally, participants felt more comfortable with simulation training than Simodont ® for both practical exercises. Eighty‐eight per cent of the participants disagreed that Simodont ® should replace conventional simulation. Conclusions: The study suggests that Simodont ® could be used as an adjunct in training dental students for pre‐clinical paediatric dentistry restorative exercises.